2009
DOI: 10.1177/1934578x0900400710
|View full text |Cite
|
Sign up to set email alerts
|

Prenylated Flavones from Artocarpus Lanceifolius and their Cytotoxic Properties against P-388 Cells

Abstract: New prenylated flavones, artoindonesianins Z-4 and Z-5, together with four known prenylated flavones, artonin E, 12-hydroxyartonin E, artobiloxanthone, and cycloartobiloxanthone, have been isolated from the methanol extract of the tree bark of Artocarpus lanceifolius. The structures of these compounds were determined on the basis of spectroscopic data, including UV, IR, 1D and 2D NMR, and mass spectra. The cytotoxic effect of the isolated compounds against murine leukemia P-388 cells is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…7 For clarity, the mechanism for formation of one enantiomer of the major diastereomer is shown in Figure 3 (See SI for detailed reaction profiles for formation of the other diastereomer and its enantiomer are reported). First, addition of the chiral catalyst results in a tetrahedral intermediate (11) with N2 poised to leave. The barrier to extrude nitrogen is low and this process is predicted to be highly exergonic, forming one major rotamer of Rh carbene (8).…”
Section: Alkyl/alkyl Stereogenic Insertion Centersmentioning
confidence: 99%
See 2 more Smart Citations
“…7 For clarity, the mechanism for formation of one enantiomer of the major diastereomer is shown in Figure 3 (See SI for detailed reaction profiles for formation of the other diastereomer and its enantiomer are reported). First, addition of the chiral catalyst results in a tetrahedral intermediate (11) with N2 poised to leave. The barrier to extrude nitrogen is low and this process is predicted to be highly exergonic, forming one major rotamer of Rh carbene (8).…”
Section: Alkyl/alkyl Stereogenic Insertion Centersmentioning
confidence: 99%
“…This facile method to generate trisubstituted benzodihydrofuran cores enables the asymmetric synthesis of multiple classes of natural products, patented biologically active small molecules, and their analogs, to be rapidly synthesized (Figure 1). [11][12][13][14][15][16][17] Previous work by Taber 18 and Doyle 19 used chiral C-H insertion centers and acceptor-substituted carbenes to create selectivity models for their respective systems. Taber demonstrated that the stereochemistry of the C-H insertion site was retained and attributed this observation to a concerted mechanism (Figure 2A).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 For clarity, the mechanism for formation of one enantiomer of the major diastereomer is shown in Figure 3 (See SI for detailed reaction profiles for formation of the other diastereomer and its enantiomer are reported). First, addition of the chiral catalyst results in a tetrahedral intermediate (11) with N2 poised to leave. The barrier to extrude nitrogen is low and this process is predicted to be highly exergonic, forming one major rotamer of Rh carbene (8).…”
Section: Table 1 Alkyl/aryl Stereogenic Insertion Centersmentioning
confidence: 99%
“…Facile access to benzodihydrofuran cores enables multiple classes of asymmetric natural products, patented biologically active small molecules, and their respective analogs to be rapidly synthesized (Figure 1). [11][12][13][14][15][16][17] Previous work by Taber 18 and Doyle 19 used chiral C-H insertion centers and acceptor-substituted carbenes to create selectivity models for their respective systems. Taber demonstrated that the stereochemistry of the C-H insertion site was retained and attributed this observation to a concerted mechanism (Figure 2A).…”
Section: Introductionmentioning
confidence: 99%